Propagação vegetativa de espécies do gênero Piper e suas potencialidades - Magevski, Gizele Cristina (2012)
The species Piper nigrum (black pepper) is widely used as a condiment, and valued worldwide. The state of Espirito Santo is the second in the national production of this species, which has great social and economic, to generate alternative income for the family farmer. However, since 1957 this culture began to be affected by a disease that attacks the root system, known as Fusarium. The disease is caused by the fungus Fusarium solani f. sp. piperis, causing the deaths of thousands of pepper plants, resulting in large losses of production and improved crop production cycle. There is still no proven technology that disease, but it is recommended that you use the graft to obtain disease resistance of the soil, allowing the cultivation of certain species in contaminated areas. It is known that native Piperaceae, such as P. aduncum L., P. arboreum, P. carniconnectivum, P. hispidum, P. hispidnervum, Piper sp and P. tuberculatum showed high resistance to infection with two isolates of Nectria haematococca f. sp. piperis, so they can be used with rootstocks. Thus this work aimed to investigate the propagation by cuttings of three species of Piperaceaes (P. arboreum Aubl. and P. mollicomum, P. amplum Kunth) with potential resistance to fusarium wilt of P. nigrum L., subsidizing therefore information for the production of rootstocks resistant to the Fusarium solani. The first experiment was related to the induction of adventitious rooting of cuttings in three Piper species (P. arboreum, P. amplum and P. mollicomum) using IBA at different concentrations (0, 2000, 4000, 6000 and 8000 mg kg-1 ). The evaluation was performed at 45 days of transplanting and the variables were analyzed: survival (%), leaf number, number of shoots and the average length of the largest bud (cm). In the second experiment, we xi tested the induction of root and shoot growth of cuttings of P. arboreum and P. amplum with the same concentrations used in the first experiment. The evaluation was performed at 90 days of cultivation and the variables were analyzed: survival (%), rooting (%), emission of shoots (%), number of root and shoot, length of roots and the largest bud (cm) and diameter of the bud (mm). The third experiment aimed to detect sources of resistance to Fusarium solani, among the different species of wild Piper propagated in this work and verify that two isolates (isolate I and II) from the pepper with symptoms of fusarium wilt, differ in their ability to infect different hosts. The species P. arboreum and P. amplum, and 98% showed 100% survival, respectively, regardless of the concentration of IBA employed. It was observed that for the rooting of the cuttings of the species P. amplum indicated 3.000 mg kg-1 IBA and for P. arboreum was linear, requiring therefore, studies with concentrations greater than 8,000 mg kg-1 of IBA. It has been demonstrated potential for resistance to both isolates tested on P. arboreum, P. amplum and P. mollicomum, but this condition has yet to be proven under field conditions.